Investigating the accuracy of digital levels and reflectorless total stations for purposes of geodetic engineering - Ashraf A.A. Beshr; Islam M. Abo Elnaga (Alexandria Engineering Journal, 2011)
In order to achieve the results that meet the specifications of a given project, like engineering surveys and deformation measurements, the knowledge of the reliability and accuracy of the surveying equipment is inevitable. Precise digital levels and reflectorless total stations are used nowadays for several applications in geodetic engineering due to their highly accurate and fast measurements in an automated measuring process. A shortcoming is that they give less accurate measurements in some cases of observations. There are several sources of errors which have an effect on the accuracy of staff reading during digital leveling such as the effect of sun, and therefore have to be investigated. The quality and accuracy of measurements of electronic surveying instruments may be affected by the capacity of instrument battery which may be worked for long time in the field. This paper investigates the effect of sun on the accuracy of digital level measurements and investigates also the effect of battery capacity on the accuracy of total station and digital levels observations. The paper is performed also to find out the effect of inclined angle of reflecting surface, its colors and types on the accuracy of reflectorless total station measurements which have a great influence on monitoring the deformation of cylindrical and domical structures. The results of practical measurements, calculations and analysis of the interesting tests using least squares theory and computer programs are also presented.